Measuring changes in family wellbeing in New Zealand 1981 to 2006 - Crothers, CH; Cotterrell, G; Von Randow, M (New Zealand Sociology, 2013)
Since the mid-1980s, New Zealand has experienced extensive economic, social and political reforms. The economic impact of these changes has been closely monitored and much commented upon. However, the social impacts of the reforms on different categories of families and households are less well understood. This article presents data from a project designed to monitor how the reforms have impacted upon these categories, via indicators of wellbeing constructed from census data. All of this reveals variable impacts by category, with single-parent family households faring worst over the 1981–2006 period.